Pengaruh Desentralisasi Fiskal, Pengangguran, Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) Kalimantan Barat : Perspektif Ekonomi Islam - Metasari Kartika; Erni Panca Kurniasih; Nina F. Dosinta; Wahid Wahid (Universitas Warmadewa, 2024)
The Human Development Index (HDI) is a main factor in determining achievement to help build the quality and welfare of human life in the sense of improving the welfare of the people. Quality human resources are the main capital that is the most basic for the development of a nation. West Kalimantan's HDI is currently ranked as low as 30th. More special review and attention is needed to analyze this. Several factors such as fiscal decentralization, poverty and unemployment can influence human development in West Kalimantan. The aim of this research is to examine and analyze the influence of fiscal decentralization, poverty and unemployment on HDI in West Kalimantan Province. The analysis will also be completed from an Islamic economic perspective in the context of human development. The research method is quantitative using secondary data. The data is then processed using eviews software. The research model was obtained after going through model testing and classical assumption testing. It is hoped that this research can provide another side of the policy approach to increasing HDI from an Islamic economic perspective.